I think it should be E.
If (y+3)(y-1) – (y-2)(y-1) = r(y-1), what is the value of y?
(1) r^2 = 25
(2) r = 5
Yes, you are right in that it would be wrong to divide by (y-1) – at least at this stage. So, let’s first simplify the expression:
(y+3)(y-1) – (y-2)(y-1) = r(y-1)
(y-1)((y+3)-(y-2)) = r(y-1)
We can rewrite the last one in the form: (y-1)*(5-r)=0. From here, we have two possibilities: y=1 or r=5. Now, it’s time to look at our statements.
From the first, we can’t say whether r=5 (it could be 5 or -5). Thus, we can’t say whether y=1 => statement is insufficient.
From the second, if r=5 then y could be any number. So, again, it’s insufficient.